"Awake" Extracorporeal Membrane Oxygenation as a Bridge to Lung Transplant. (July 2016) - Kearns, Sara K.; Hernandez, Omar O.
Abstract : ABSTRACT : Mortality of patients awaiting lung transplant remains a significant problem as the number of patients on the waiting list far surpasses the number of donor organs available. Interest in the use of "awake" extracorporeal membrane oxygenation (ECMO) as a bridge to lung transplant has emerged because this strategy offers several benefits over mechanical ventilation. This article provides a review of relevant literature and discusses indications and complications of awake ECMO therapy, cannulation strategies, and nursing considerations for this patient population.